2002
DOI: 10.1103/physreve.66.065202
|View full text |Cite
|
Sign up to set email alerts
|

Chaos-based secure communications in a large community

Abstract: One-way coupled map lattices are used for cryptography in secure communication, based on spatiotemporal chaos synchronization. The sensitivity of synchronization between the encryption and decryption systems can be adjusted by varying the system size. With a suitable parameter combination, the cryptosystem can reach optimal trade-off of security and performance, i.e., it shows high security (resistant against the public-structure and known-plaintext attacks) together with fast encryption (and decryption) speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 20 publications
1
74
0
1
Order By: Relevance
“…OCML as a theoretical model of spatiotemporal phenomena has attracted much attention in secure communications [5][6][7][8]. In comparison with low-dimensional chaos, spatiotemporal chaos is much more complex in dynamics.…”
Section: Cryptosystem Incorporating Lissajous Map With Ocmlmentioning
confidence: 99%
See 1 more Smart Citation
“…OCML as a theoretical model of spatiotemporal phenomena has attracted much attention in secure communications [5][6][7][8]. In comparison with low-dimensional chaos, spatiotemporal chaos is much more complex in dynamics.…”
Section: Cryptosystem Incorporating Lissajous Map With Ocmlmentioning
confidence: 99%
“…[15], sharing short time unpredictability, longer period, and better random properties. In other words, the internal states are transformed into a very complex dynamics, i.e., key streams, by non-linear functions with non-invertible characteristics such as INT and MOD operations [5][6][7][8]. However, we have found that this class of cryptosystem still suffers from the problem of degeneration, and the differential-like chosen cipher attack (DCCA) can break the prototype of such cryptosystems with ignorable computational costs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the short period problem of CRCTs can be practically solved by applying coupled (spatiotemporal) chaotic systems with a sufficiently large N . This is one of several most important reasons why the system in [22] may reach very high security. The phenomenon of small number of periodic orbits of CRCT is also observed for coupled maps.…”
Section: Periodicity Of Chaotic Coupled Map Lattices In Computer Realmentioning
confidence: 99%
“…In Ref. 22, the authors suggested to use spatiotemporal chaotic systems for cryptography and declared that they can reach very high level of security, it is then interesting to investigate the periodicity of CRCTs of such spatiotemporal systems. Let us extend the single map (1) to one-way coupled map lattice…”
mentioning
confidence: 99%
“…However, recent studies show that the performance of these systems is very poor and insecure [10,11]. The insecurity results mainly from the insensitivity of synchronization to system parameters [12]. Recently, discrete chaotic communication systems have been given much more attention [13][14][15].…”
Section: Introductionmentioning
confidence: 99%